Analisis Putusan Pengadilan dalam Perkara Tindak Pidana Pencemaran Udara - Susi Sopiani (Savana, 2024)
Air pollution is one part of physical environmental pollution. Air pollution according to the Government Regulation on air pollution control is the entry or introduction of substances, energy, and/or other components into ambient air by human activities, so that the quality of ambient air decreases to a certain level that causes ambient air to be unable to fulfill its function. The research method used is to use a type of normative legal research method, by examining library materials or secondary data which include primary legal materials, secondary legal materials and tertiary legal materials using Decision Number 68/Pdt.G/LH/2022/PN Rap. The results of the study, namely the lawsuit was rejected by the Court and the impact was air pollution, namely respiratory disorders, cardiovascular disease, impaired fetal development, decreased lung function, and chronic diseases. Conclusion Air is very important because it provides oxygen and other gases that are essential for all life on earth. Air pollution or contamination is the introduction of other components into the air, either by human activities directly or indirectly or due to natural processes. The impacts of this pollution include respiratory disorders, cardiovascular disease, impaired fetal development, decreased lung function, and chronic diseases. Suggestions Palm oil mills need to adopt more effective pollution control technologies to reduce emissions of hazardous materials into the air. Local governments and environmental regulatory agencies must ensure that palm oil mills comply with all applicable environmental regulations and standards. Local communities must be empowered and educated about their rights and how to advocate for a healthy environment.